Human- Elephant Conflict and Environmental Journalism in Sri Lanka - Tennakoon, S.D.R.; Mahees, M.T.M. (My University, 2019)
This study examines the human-elephant conflict in the context of environmental journalism in Sri Lanka. The paper is based on empirical study and reviews of the relevant literature in environmental sociology and political ecology. The changing political economic policies and development activities have affected the reciprocal interaction between society and nature resulting many socio-environmental crises such as the human-elephant conflict which has become a threat to the elephant population as well as to human beings. The main objective of the paper is to assess the human-elephant conflict in the context of environmental journalism in Sri Lanka. The paper draws relevant literature from archives and print media. Content analysis of newspaper articles of Sunday Lankadeepa, Sunday Observer and Sunday Thinakaran published from 2009 to 2013 was carried out based on stratified sampling. The qualitative information with regard to environmental journalism on the humanelephant conflict was collected from 15 in-depth interviews based on purposive sampling. The findings revealed the main cause for the human-elephant conflict is rapid increase in human population, deforestation in the name of development, conspicuous consumption and socio - economic agricultural policies. The increase of rural habitation has resulted in invading the natural elephant territories by humans. This has become the underline cause for the human elephant conflict in many parts of Sri Lanka. Moreover, the government agricultural economic policies have a major impact on destroying the elephants’ natural habitat. Due to the loss of their habitats and habitat fragmentation, elephants have begun to roam around rural habitation and migrate from place to place attacking and destroying cultivated land and people. On the other hand, media highlights the human-elephant conflict in comparison with other environmental issues sensationalizing the conflict by highlighting and creating a critical socioenvironmental issue on the mass culture.
Keywords: human-elephant conflict, environmental journalism, natural habitat